Comparison between orthodontic micro-implants and dental units as anchorages for tooth retraction in dogs - Chawshil, Omer Fawzi; AlMaarof, Rafah Hatam; Jasim, Fadhil Yasen (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: Dental units, extra oral devices and mini-implants are the main types of anchorage that are used in orthodontic treatment. The aim of this study was to compare between mini-implants and dental unites as anchorage.Methods: This study used seven dogs wearing orthodontic appliances in the right and left sides of the maxilla for 40 days to retract the 3rd incisors toward the canines. On right side, canine was used as dental anchorage to retract the 3rd incisor by nickel-titanium closed coil spring along a straight arch wire. On the left side, mini-implant between the roots of canine and 1st premolar was used as skeletal anchorage. Different clinical measurements were done on the stone casts and photographs of maxillary dental arch for each dog before and after tooth retraction to assess the effectiveness of each anchorage type on the same animal.Results: Clinical measurements revealed a highly significant difference between dental and mini-implant sides. The mini-implant side showed less loss of anchorage than dental side, while the extrusion was higher in retracted tooth of mini-implant side than in dental sideConclusion: This study showed that the mini-implants provide more stable anchorage units than the teeth but cause more extrusion in the moving tooth.